A Akuntabilitas Fiskal Vs Akuntabilitas Sosial Pengelolaan Keuangan Desa - Baiq Rosyida Dwi; Wirawan Suhaedi; Biana Adha Inapty; Robith Hudaya (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2022)
The aims of this study is to determine the level of application of fiscal accountability and social accountability of village financial management, and to compare the application of both. The research is a qualitative research with a phenomenological approach. Data was collected through interviews of informans are involving in village financial management and documentation of the Village Budget Realization Report (LRA). The results showed that the fiscal accountability was less quality. This is based on the behavior of village government financial report compilers who report dishonest and accurate spending. Meanwhile, social accountability, both supply and demand side, is determined by the attitudes, habits and views of village financial management officials. Quality of social accountability practices is similar with quality of fiscal accountability practices. However, taking into account the phenomena that occur, the degree of social accountability will determined by the quality of fiscal accountability. Keyword : Fiscal Accountability, Sosial Accountability